STRATEGY OF TOURISM SUPPLY CHAIN DEVELOPMENT IN MARINE TOURISM DESTINATION MADASARI BEACH PANGANDARAN REGENCY WEST JAVA - Tiffany Chairunnisa Ramadhania (LPSDI Bina Patria, 2024)
The objective of this research were to produce a strategy for developing tourism supply chains in marine tourism destination Madasari Beach Pangandaran Regency, West Java. This research identifies and analyzes how the existing conditions of tourism and business products/services are involved in the production group (accommodation service business, transportation service business, tourism travel business, food and craft services business, management of tourist attraction in a destination). This research uses an analysis of external and internal environmental situations (TOWS) to find out how the existing condition of Madasari Beach based on the sequence of strategies in TOWS analysis which will serve as a reference for strategic planning output on developing tourism supply chains. The results show that Madasari Beach still has various weaknesses in developing of tourism supply chain. The results of the analysis of external and internal situations show that the position of Madasari Beach is in quadrant 3 with a negative x and a positive y. The suggestions in this research are to improve the competence of human resources in the field of service and tourism product development for tourism service business, local communities, and government elements, adding facilities and accessibility that can support the implementation of tourism activities in Madasari Beach. and partnering with tourism service businesses in other tourist attractions outside the Madasari Beach region, determining form and building management or institution for tourism destination operational in order to increase competitiveness and increase tourist visits to Madasari Beach.